ANALISA PENDAPATAN DAN PERSEPSI PETANI KERAMBA TERHADAP KEBERADAAN PT.AQUAFARM NUSANTARA (Studi Kasus : Petani Keramba Dikecamatan Girsang Sipanganbolon Kabupaten Simalungun) - Ruth Casarena Saragih; Ramli Ramli (Departemen Ekonomi Pembangunan USU, 2013)
The purposes of this research is to analyze the income and perception of cage farmersagainst existence PT.Aquafarmnusantara on subdistrictGirsangsipanganbolon regencySimalungun .The data used in this study were primer and obtained from 60 cage farmers bysimple random sampling. The analysis method used in this study is Quantitative DescriptiveAnalysis and Path analysis. The test of validity and reliability of the instrument based on value by 0,3%. The result shows that level of education, spacious cages, experience, feed of fish and fingerlings significant to total fish production and level of education, spaciouscages, experience, feed of fish, fingerlings and total fish production significant to level of income of cage farmers and the result of validity and reliability test shows that the questions of perception are valid and reliable.Keywords: Level of Income, Total Fish Production, Perception, Level of Education, Spacious, Cages, Experience, Feed of Fish, Fingerlings.